Hubungan Persepsi Warga Belajar terhadap Strategi Pengelolaan Tutor dengan Hasil Belajar pada Kejar Paket C di PKBM Merah Putih Kecamatan 2x11 Kayutanam - Mulyana Safitri; Wisroni Wisroni; Jalius Jalius (Universitas Negeri Padang, 2018)
This research is motivated by the low learning outcomes of citizens learning Paket C in PKBM Merah Putih Kayutanam. This study aims to describe the perceptions of the learners on the management strategies used by the tutors in the C-class equivalency learning group and to illustrate the perceptions of the learners to the learning management strategy of the tutor with the learning outcomes in the C-class equivalent group learning group. This study is a quantitative correlational descriptive study with respondents of 20 participants of the study group Paket C at PKBM Merah Putih Kayutanam. Data collection techniques in this study using questionnaires and data collection tools using questionnaires. The results revealed that there is a significant relationship between the perceptions of learners to learning strategies tutors with learning outcomes.